(untitled)
In a 21-point finite difference scheme, assign suitable interpolation values to the fictitious node points. The numerical eigenvalues are then of O(h^2) precision. But the corrected value λ_h=λ_h+h^26λ_h^32 and extrapolation λ_h=43λ_λ2 -13λ_h can be proved to have O(h^4) precision. , number=3, journal=Journal of Computational Mathematics, year=2018, month=May, pages=267–271